2011
DOI: 10.1167/iovs.09-4809
|View full text |Cite
|
Sign up to set email alerts
|

Biocidal Efficacy of Silver-Impregnated Contact Lens Storage Cases In Vitro

Abstract: Current silver-impregnated CL storage cases show variation in their in vitro antimicrobial activity. Broadly, the MicroBlock case demonstrated robust activity against most Gram-negative bacteria, whereas the i-clean case was more effective against S. aureus. Silver-release data suggest different modes of action for different cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…62 Fungi can be resistant to the activity of several contact lens multipurpose disinfecting solutions. 63 Furthermore, a recent study investigating in vitro antimicrobial activity of three commercially available silver impregnated contact lens cases revealed high activity against bacteria, but all the lens cases were essentially ineffective against C. albicans after 6, 10, and 24 hours, 64 and only one lens case showed limited activity (0.5 log) against Fusarium solanii. 43 In this study we have demonstrated that the melimine-coated lenses produced at least one log inhibition against both Candida and Fusarium strains, indicating the possibility of controlling colonization of lens surfaces by fungi as well as bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…62 Fungi can be resistant to the activity of several contact lens multipurpose disinfecting solutions. 63 Furthermore, a recent study investigating in vitro antimicrobial activity of three commercially available silver impregnated contact lens cases revealed high activity against bacteria, but all the lens cases were essentially ineffective against C. albicans after 6, 10, and 24 hours, 64 and only one lens case showed limited activity (0.5 log) against Fusarium solanii. 43 In this study we have demonstrated that the melimine-coated lenses produced at least one log inhibition against both Candida and Fusarium strains, indicating the possibility of controlling colonization of lens surfaces by fungi as well as bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…For the three cases examined, Microblock, i-clean, and Nano-case, the antimicrobial activities were different (P Յ 0.001), with the Nanocase demonstrating the greatest activity, decreasing cell counts by 0.2 Ϯ 0.3 logs. Only the Microblock case showed silver release over 28 days (70).…”
Section: Resistance To Metalsmentioning
confidence: 99%
“…The biocidal efficacies of three silver-impregnated contact lens storage cases (Microblock, i-clean, and Nano-case) against S. maltophilia were tested (70). Case wells contained cell counts (10 3 to 10 6 CFU/ml) that were incubated for 6 to 24 h at 25°C.…”
Section: Resistance To Metalsmentioning
confidence: 99%
“…A comparison of organoselenium (1.0%) polypropylene contact lens case coupon versus the results of the best of the silver impregnated lens cases tested by 6 is the following (it should be noted that the silver data are for bacterial concentration in solution; we found the same concentration for our solution measurements as we did for the bacteria on the polypropylene, i.e., if there was no bacteria on the organoselenium polypropylene, there was none in solution): (1) MicroBlock (CIBA Vision) showed a reduction in P. aeruginosa of 2.4 logs, whereas organoselenium polypropylene contact lens case coupon was 7.3 logs (100%); S. marcescens reduction of 3.3 logs, whereas organoselenium polypropylene contact lens case coupon showed the Several stacks were acquired from each surface of the polymer, and the images were analyzed using the COMSTAT program.…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available silver cases have been recently studied for their ability to inhibit bacterial growth in the solution stored in the case. 6 The authors found that the best reduction in bacterial binding from the different case types was the following: Staphylococcus aureus, 5.4 logs; Pseudomonas aeruginosa, 2.4 logs; Serratia marcescens, 3.3 logs; Delftia acidovorans, 2.8 logs; Fusarium solani, 0.5 logs; and Stenotrophomonas maltophilia only 0.2 logs. In an in vivo study where the cases used by patients were monitored, it was found that 70% of the cases were contaminated with biofilm irrespective of whether or not the case was impregnated with silver.…”
mentioning
confidence: 99%